Especiação de urânio em águas tratada de drenagem ácida de mina usando a técnica de difusão em filmes finos por gradiente de concentração (DGT) - Pedrobom, Jorge Henrique [UNESP] (2016)
One of the major concerns in uranium mining areas is the Acid Mine Drainage (AMD). This process occurs spontaneously and uncontrollably in Poços de Caldas Ore Industrial Complex (CIPC). DAM can generate levels of uranium species higher than the maximum allowed values for water bodies discharge. During the DMA process, uranium is possibly in the form of uranyl oxides and hydroxides and after reaching water bodies, it changes to species which contain carbonate and sulfate groups. The determination of concentration and lability of these species is important to evaluate the metal biogeoavailability to the water system. The Diffusion Gradients in Thin Films Technique (DGT) has been used for the quantification of labile metals and their speciation in several types of sample. In this research, DGT technique was used in lab with different binding layers to evaluate its suitability to DAM waters and uranium mining surrounding tributaries. Therefore, the developed method was performed in situ along the solid phase extraction technique (SPE) to assess the lability of uranium species present in the system. The results obtained by DGT technique showed that a large part of the uranium present in the samples is its labile form. Also, these results were consistent with speciation via the MINTEQ software. Moreover the results obtained by SPE were not consistent with those from DGT technique, probably because of the saturation of the binding phase or due to the different residence times of ions in different techniques.